The Efforts Of Teachers In Addressing Selective Mutism Disorder In Children (A Qualitative Descriptive Study at Lembayung Kindergarten, Bengkulu City) - Balqis, Nopria Putri; Bendriyanti, Rita Prima; Mayasari, Henni; Pebriani, Ela (Early Childhood Research and Practice, 2025)
The purpose of this research is to examine the efforts of teachers in addressing selective mutism disorders in children at TK Lembayung, Bengkulu City. The type of research used in this study is descriptive qualitative research. The methods of data collection used are interviews, observations, and documentation. The data sources are the teachers and the principal of TK Lembayung in Bengkulu City, as well as documentation in the form of photographs taken during interviews with the teachers and principal. The data reduction involved recording the results of the interviews with the teachers and principal, coding the data according to the information provided by the informants, data display involved explaining the results of the interviews with the teachers and principal, and data verification involved rethinking the interview results, reviewing field notes, reconsidering observation data, and findings in the field in order to draw conclusions from the research conducted. The results of this study describe the efforts of teachers in addressing disturbances.